Integrating Arabic Curriculum and Pesantren Cultural Identity in the Arabic Education Program of UNSIQ - Aulia Rahman, Rifqi; Bahruddin , Uril; Nurhadi, Nurhadi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
The Arabic language curriculum of the Arabic Language Education Program at pesantren-based universities has not fully accommodated the cultural values of pesantren as a local identity embedded within the learning process. Consequently, a dilemma arises between the effort to strengthen Arabic language proficiency in the academic sphere and the preservation of pesantren cultural traditions, which are the soul of education in this environment. This study aims to explore the relationship between the Arabic language curriculum and pesantren cultural identity within higher education, focusing on the Arabic Language Education Program (PBA) at Universitas Sains dan Al-Qur'an (UNSIQ). Employing an educational anthropology approach, this research analyzes how the curriculum shapes the habit, cultural capital, and identity of students with pesantren backgrounds. Utilizing qualitative methods, data were gathered through participatory observations, in-depth interviews, and document studies involving lecturers, students, and curriculum developers. The findings reveal that the curriculum emphasizes not only linguistic but also pedagogical aspects, and it integrates Islamic and socio-cultural values of pesantren. The Arabic curriculum at PBA UNSIQ serves as a cultural reproduction mechanism that reinforces student identity through the use of the yellow book-based learning method, traditional pesantren evaluation systems, and socio-religious approaches in lectures. However, challenges remain, particularly in accommodating non-pesantren students who must adapt to the pesantren-based academic traditions. To foster a more inclusive learning environment, PBA UNSIQ integrates modern learning methods, technological utilization, and mentoring programs for students with diverse educational backgrounds.